Multifunctional gradient coating based on 3D printed implants and method of manufacture
Patent Information
- Application Number
- CN202611228244.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-16
AI Technical Summary
然而,尽管机械适配性优异,其表面生物活性不足、易引发术后感染及长期耐腐蚀性缺陷仍严重制约临床效果:纯钛表面天然骨诱导性弱,需依赖涂层引入羟基磷灰石(HA)等活性成分增强骨整合;植入物作为异物易滋生金黄色葡萄球菌等致病菌,诱发骨髓炎;长期体液环境(pH波动、氯离子侵蚀)中,多孔结构内部可能发生微腐蚀并释放金属离子,威胁周围组织健康
本申请提供的基于3D打印植入物的多功能梯度涂层,首先,多孔且掺入钙磷离子的TiO2底层通过等离子体电解氧化(PEO)原位生成,与钛合金基体形成高强度的冶金结合。其微米级多孔形貌为上层的等离子喷涂颗粒提供了极佳的机械锁合锚点,显著解决了传统喷涂涂层易剥落的技术难题。其次,中间层利用钙磷陶瓷的骨传导性引导成骨细胞粘附,并利用分散的银纳米颗粒实现广谱抗菌。由于中间层表面存在微观粗糙度与起伏,外层致密的纳米级TiN薄膜保形包裹后,在局部形成了纳米级的离子扩散通道,或在后续热处理及液相负载时产生微观热应力释放位点,允许银离子(Ag+)以安全、缓慢的速率向外控释,既避免了银的细胞毒性,又兼顾了长期抗菌效能。最后,原子层沉积(ALD)制备的致密纳米级TiN表层具备极佳的保形性,能够渗透进入3D打印植入物的深层孔隙内部,作为物理屏障有效阻隔氯离子侵蚀,防止体液环境对基体造成长期微腐蚀。三层结构协同作用,解决了传统涂层结合力弱、功能单一及耐腐蚀性差的矛盾,实现了植入物在复杂生理环境下的长期稳定与生物安全。
Smart Images

Figure CN122912181A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the interdisciplinary field of biomedical materials and surface engineering, specifically to a multifunctional gradient coating based on 3D printed implants and its preparation method. Background Technology
[0002] 3D-printed titanium alloy implants have become an important choice in the field of bone defect repair due to their unique advantages of personalized shape design and gradient porous structure (porosity 50%-80%, pore size 200-600μm). Their porous structure can simulate the mechanical environment of cancellous bone to promote cell infiltration, while their personalized shape can precisely match the morphology of complex bone defects. However, despite their excellent mechanical adaptability, their insufficient surface bioactivity, susceptibility to postoperative infection, and long-term corrosion resistance still seriously limit clinical efficacy: the natural osteoinductive properties of pure titanium surface are weak, requiring the introduction of active ingredients such as hydroxyapatite (HA) through coating to enhance osseointegration; as foreign bodies, implants are prone to the growth of pathogenic bacteria such as Staphylococcus aureus, inducing osteomyelitis; in the long-term body fluid environment (pH fluctuations, chloride ion erosion), micro-corrosion may occur inside the porous structure, releasing metal ions and threatening the health of surrounding tissues.
[0003] Existing surface coating technologies struggle to adapt to the complex characteristics of 3D-printed gradient porous structures, facing three major bottlenecks: First, there is a conflict between uniformity and bonding strength; traditional plasma spraying easily creates "coating voids" within the pores, and low-temperature processes such as sol-gel achieve bonding strength of less than 10 MPa. Second, balancing multiple functions is difficult; antibacterial properties and bone integration are incompatible, making it difficult for a single coating to achieve both simultaneously. Third, adaptability to complex structures is poor; spraying processes are limited by "visibility restrictions" and cannot cover deep pores. Therefore, there is an urgent need to develop novel gradient coating technologies suitable for 3D-printed gradient porous structures. Summary of the Invention
[0004] To address the problems existing in the prior art, this invention provides a multifunctional gradient coating and preparation method for 3D printed implants. By combining plasma electrolytic oxidation (PEO), plasma spraying (APS), and atomic layer deposition (ALD) synergistic processes, it achieves synergistic optimization of osseointegration, antibacterial and corrosion resistance properties, while ensuring the uniformity and high bonding strength of the coating on complex porous surface structures, providing a safe and efficient surface modification solution for personalized implants.
[0005] This invention is achieved through the following technical solution: In the first aspect, this application provides a multifunctional gradient coating based on 3D printed implants, comprising a TiO2 bottom layer, a calcium phosphate ceramic-silver composite intermediate layer and a TiN surface layer arranged sequentially from the inside out; The TiO2 bottom layer has a porous structure and is doped with calcium and phosphorus ions; The calcium phosphate ceramic-silver composite intermediate layer is composed of a calcium phosphate ceramic matrix and silver nanoparticles dispersed therein. The TiN surface layer is a dense, corrosion-resistant layer.
[0006] Preferably, the thickness of the calcium phosphate ceramic-silver interlayer is 20-30 μm, and the mass percentage of the silver nanoparticles is 3%-10%.
[0007] Preferably, the calcium phosphate ceramic matrix includes at least one of hydroxyapatite, β-tricalcium phosphate, or biphasic calcium phosphate.
[0008] Preferably, the TiN surface layer is further loaded with bioactive glass particles.
[0009] Secondly, this application provides a method for preparing a multifunctional gradient coating based on a 3D printed implant, comprising the following steps: Step 1: Prepare a composite coating on the surface of the implant. The composite coating consists of a TiO2 bottom layer, a calcium phosphate ceramic-silver composite intermediate layer, and a TiN surface layer from the inside out. The implant is subjected to plasma electrolytic oxidation in an electrolyte containing calcium and phosphorus ions to generate a porous TiO2 bottom layer in situ on the implant surface, while calcium and phosphorus ions are incorporated into the TiO2 bottom layer. Calcium phosphorus ceramic powder is mixed with silver nanoparticles, and the mixed powder is deposited on the surface of the TiO2 bottom layer by plasma spraying process to form a phosphorus ceramic-silver composite intermediate layer. Atomic layer deposition was used to deposit a TiN surface layer on the surface of the phosphorus ceramic-silver composite intermediate layer using titanium and nitrogen precursors as raw materials. Step 2: Anneal the composite coating obtained in Step 1. After annealing, load bioactive glass particles onto the TiN surface using a liquid phase deposition process to obtain the multifunctional gradient coating.
[0010] Preferably, step 1 is preceded by a pretreatment step of the implant surface: The implant surface is sandblasted with sandblasting particles, and then the sandblasted implant is immersed in an acidic solution for acid etching for 1-5 minutes.
[0011] Preferably, the plasma electrolytic oxidation method is as follows: The implant is immersed in an electrolyte for plasma electrolytic oxidation at a voltage of 250-400V for 3-10 minutes. The concentration of calcium ions in the electrolyte is 0.05-0.2 mol / L, and the concentration of phosphorus ions is 0.02-0.1 mol / L.
[0012] Preferably, the atomic layer deposition method is as follows: The pulse time ratio of the titanium precursor to the nitrogen precursor is 1:(1-3), the deposition temperature is 150-350℃, and the number of cycles is 300-800.
[0013] Preferably, in step 2: the annealing temperature is 350-450℃, the time is 1-3 hours, and the annealing atmosphere is an inert gas atmosphere or a vacuum atmosphere.
[0014] Preferably, the wet deposition process is at least one of dip-coating, spin-coating, or spray deposition.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The multifunctional gradient coating for 3D-printed implants provided in this application firstly involves a porous TiO2 sublayer incorporating calcium and phosphorus ions, generated in situ via plasma electrolytic oxidation (PEO), forming a high-strength metallurgical bond with the titanium alloy substrate. Its micron-scale porous morphology provides excellent mechanical anchoring points for the plasma-sprayed particles in the upper layer, significantly solving the technical problem of easy peeling of traditional sprayed coatings. Secondly, the intermediate layer utilizes the osteoconductive properties of calcium and phosphorus ceramics to guide osteoblast adhesion and employs dispersed silver nanoparticles to achieve broad-spectrum antibacterial activity. Due to the microscopic roughness and undulations on the surface of the intermediate layer, the outer dense nanoscale TiN film, after conformal encapsulation, forms nanoscale ion diffusion channels locally, or generates microscopic thermal stress release sites during subsequent heat treatment and liquid-phase loading, allowing silver ions (Ag) to diffuse. + The controlled release of silver at a safe and slow rate avoids its cytotoxicity while maintaining long-term antibacterial efficacy. Finally, the dense nanoscale TiN surface layer prepared by atomic layer deposition (ALD) possesses excellent shape retention, allowing it to penetrate deep into the pores of the 3D-printed implant. This acts as a physical barrier, effectively preventing chloride ion corrosion and long-term micro-corrosion of the substrate by bodily fluids. The synergistic effect of the three-layer structure resolves the contradictions of weak adhesion, limited functionality, and poor corrosion resistance in traditional coatings, achieving long-term stability and biosafety of the implant under complex physiological environments. Attached Figure Description
[0016] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 This is a flowchart of the multifunctional gradient coating preparation method of the present invention. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. The components of the embodiments of this application described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0019] Therefore, the following detailed description of the embodiments of this application provided in the accompanying drawings is not intended to limit the scope of the claimed application, but merely to illustrate selected embodiments of the application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.
[0020] See Figure 1 A method for preparing a multifunctional gradient coating based on 3D printed implants includes the following steps: Step 1: Pre-treat the implant surface to improve the adhesion between the implant and the coating; Step 2: Prepare a composite coating on the substrate. The composite coating consists of a TiO2 bottom layer, a calcium phosphate ceramic-silver composite intermediate layer, and a TiN surface layer from the inside out.
[0021] Using a pretreated 3D-printed titanium alloy implant as a substrate, a porous TiO2 layer is generated in situ on the surface of the titanium alloy through a plasma electrolytic oxidation process, while calcium and phosphorus ions are introduced into the coating to enhance bioactivity.
[0022] Using a pretreated 3D-printed titanium alloy implant as a substrate, a porous TiO2 layer doped with calcium and phosphorus was generated in situ via plasma electrolytic oxidation (PEO). A mixed powder of calcium and phosphorus ceramic powder and silver nanoparticles was deposited on its surface using plasma spraying (APS) to form an intermediate layer. Finally, a dense nanoscale TiN surface layer was deposited on the intermediate layer using atomic layer deposition (ALD) to improve long-term corrosion resistance.
[0023] Step 3: Anneal the composite coating obtained in Step 2 to promote interfacial diffusion between layers; then, load a small amount of bioactive glass onto the surface by electrophoretic deposition to further enhance the osseointegration capacity of the coating.
[0024] In some embodiments, the implant surface pretreatment method is as follows: S1.1. The surface of the 3D printed titanium alloy implant is sandblasted with sandblasting particles (particle size 50-100μm) at a sandblasting pressure of 0.3MPa to achieve a surface roughness Ra of 3-5μm.
[0025] S1.2 Immerse the sandblasted implant in an acidic solution for acid etching for 1-5 minutes. The acid etching removes the natural oxide layer on the surface of the titanium alloy, exposing the fresh titanium surface and forming nano-nucleation sites on the surface.
[0026] Furthermore, the sandblasting particles are at least one of alumina particles, white corundum, and silicon carbide; Furthermore, the acidic solution is a mixed solution of HF / HNO3 or HF / H2SO4; The acid etching process should last 1-5 minutes. The mass ratio of HF to HNO3, or HF to H2SO4, is 1:(2-5).
[0027] A multi-scale micro-roughened structure was constructed on the substrate surface through a combined pretreatment of sandblasting roughening and acid etching activation, increasing the surface roughness of the implant and exposing the fresh titanium surface. The micron-scale uneven structure formed by sandblasting enhances the mechanical interlocking of the coating, while the nano-scale micro-protrusion structure formed by acid etching provides more nucleation sites for the coating. This multi-scale surface structure is conducive to the strong bonding between the subsequent coating and the substrate, laying the foundation for the preparation of coatings with high bonding strength.
[0028] In some embodiments, the method for generating a porous TiO2 underlayer in situ on the surface of a titanium alloy using plasma electrolytic oxidation is as follows: S2.1. Using deionized water as a solvent, prepare an electrolyte containing calcium and phosphate salts, wherein the concentration of calcium ions is 0.05-0.2 mol / L and the concentration of phosphate ions is 0.02-0.1 mol / L, and stir until completely dissolved. The calcium and phosphate ions in the electrolyte provide bioactive components for the subsequent coating.
[0029] The calcium salt is at least one of Ca(NO3)2, Ca(H2PO4)2, Ca3(PO4)2 or Ca(CH3COO)2; The phosphate salt is at least one of NaH2PO4, H3PO4 or (NH4)3PO4.
[0030] S2.2. Immerse the pretreated implant from step 1 in the electrolyte and treat it using a plasma electrolytic oxidation device. The treatment voltage is 250-400V and the treatment time is 3-10 minutes to generate a porous TiO2 layer in situ on the titanium alloy surface.
[0031] S2.3 After the treatment is completed, the implant is removed and rinsed with deionized water to remove residual electrolyte on the surface, resulting in a porous TiO2 substrate with a thickness of 5-10 μm and a pore size of 1-3 μm.
[0032] A TiO2 ceramic layer was in-situ generated on the surface of a titanium alloy using a plasma electrolytic oxidation process. Under the action of high-voltage plasma discharge, the titanium alloy surface underwent melting, oxidation, and rapid solidification, forming a porous structure metallurgically bonded to the substrate. The Ca in the electrolyte... 2+ and PO4 3- During the discharge process, the material is incorporated into the coating, imparting initial biological activity to the underlying layer. The porous structure provides anchoring points for the subsequent plasma-sprayed intermediate layer, significantly improving the bonding strength between the intermediate layer and the underlying layer compared to direct spraying.
[0033] In some embodiments, the calcium-phosphorus ceramic-silver composite interlayer is prepared as follows: S3.1 Mix calcium phosphate ceramic powder (particle size 30-50μm) and silver nanoparticles (particle size 20-30nm) at a mass ratio of 3%-10% by mechanical mixing to ensure uniform adhesion or embedding of silver nanoparticles on the surface of hydroxyapatite particles.
[0034] S3.2. Use plasma spraying equipment to deposit the mixed powder onto the surface of the porous TiO2 layer. The spraying power is 25-40kW, the powder feeding rate is 2g / min, and the spraying distance is controlled at 100-150mm.
[0035] S3.3 After spraying, allow it to cool naturally to obtain a calcium phosphate ceramic-silver composite intermediate layer with a thickness of 20-30μm.
[0036] Furthermore, the calcium phosphate ceramic powder is at least one of hydroxyapatite powder, β-tricalcium phosphate powder, or biphasic calcium phosphate powder.
[0037] Hydroxyapatite and silver nanoparticles were co-deposited onto the substrate surface via plasma spraying. Hydroxyapatite possesses excellent osteoconductivity and osteoinductive properties, promoting osteoblast adhesion, proliferation, and differentiation. Silver nanoparticles, by releasing silver ions, disrupt bacterial cell membranes and DNA replication, endowing the coating with broad-spectrum antibacterial properties. The combination of hydroxyapatite and silver nanoparticles avoids the functional limitations of a single coating, achieving a synergistic effect of bioactivity and antibacterial performance.
[0038] In some embodiments, the TiN surface layer is prepared as follows: The implant is placed in an atomic layer deposition reaction chamber, using titanium and nitrogen precursors as raw materials. The pulse time ratio of titanium precursor to nitrogen precursor is 1:(1-3), the deposition temperature is 150-350℃, and the number of cycles is 300-800. The titanium and nitrogen precursors are alternately pulsed, and after each pulse, a purge is performed to remove unreacted precursors and byproducts.
[0039] After deposition, a TiN surface layer with a thickness of 5-8 μm and a grain size of less than 10 nm is obtained.
[0040] The titanium precursor is at least one of TiCl4, tetra(dimethylamino)titanium, or tetra(ethylmethylamino)titanium; The nitrogen precursor is at least one of NH3, N2 / H2 plasma, or N2 plasma.
[0041] Utilizing the self-limiting surface reaction properties of atomic layer deposition (ALD), a uniformly thick, dense, and non-porous TiN film is formed on the surface of complex porous structures. TiN possesses extremely high chemical stability and corrosion resistance; as a surface layer, it effectively blocks the diffusion of chloride ions and oxygen molecules from body fluids into the coating interior, protecting the underlying and intermediate layers and significantly improving the long-term corrosion resistance of implants. The excellent conformability of ALD ensures that even the deep pores of porous structures are uniformly covered.
[0042] In some embodiments, the annealing treatment method for the composite coating is as follows: The obtained composite coating was placed in a muffle furnace and annealed at 350-450℃ for 1-3 hours to promote interfacial diffusion between the TiO2 underlayer and the calcium phosphate ceramic-silver intermediate layer, eliminate residual stress, and improve the interlayer bonding strength.
[0043] Furthermore, the annealing atmosphere is an inert gas atmosphere or a vacuum atmosphere to prevent coating oxidation.
[0044] In some embodiments, the deposition method of the bioactive glass is as follows: Bioactive glass particles are deposited on the surface of annealed TiN using a wet deposition process, wherein the wet deposition process is at least one of dip-coating, spin-coating, or spray deposition.
[0045] When using the dip-lift method: Immerse the annealed implant in a suspension containing bioactive glass particles, lift at a speed of 1-5 mm / s, immerse for 30-90 seconds, and repeat the lifting 1-3 times.
[0046] When using the spin coating method: a suspension containing bioactive glass particles is dropped onto the TiN surface and spin-coated at a speed of 500-2000 rpm for 30-90 seconds, and then dried at 60-80℃ for 10-30 minutes.
[0047] When using the spray deposition method: a suspension containing bioactive glass particles is uniformly sprayed onto the TiN surface using a spraying device. The spraying distance is 10-20 cm and the spraying time is 10-30 seconds, followed by natural drying.
[0048] In some embodiments, the bioactive glass particles have a particle size of less than 1 micrometer, and the mass concentration of bioactive glass in the suspension is 0.2-1.0%.
[0049] Annealing promotes atomic diffusion between layers, eliminates residual stress generated during plasma spraying and atomic layer deposition, and improves interlayer bonding. The electrophoretically deposited bioactive glass particles contain components such as SiO2, CaO, and P2O5, which can release silicon and calcium ions in body fluids, further stimulating osteoblast activity and enhancing the coating's osteointegration capacity.
[0050] Example 1 The matrix is a 3D-printed Ti6Al4V porous implant for cranioplasty with a porosity of 50% and a pore size of 200μm.
[0051] A method for preparing a multifunctional gradient coating based on 3D printed implants includes the following steps: Step 1: Use silicon carbide particles (50μm in diameter) for sandblasting at a pressure of 0.3MPa to achieve a surface roughness Ra of 3μm; then immerse in a mixed solution of HF / H2SO4 (volume ratio 1:2) for acid etching for 1 minute.
[0052] Step 2: Prepare the composite coating: An electrolyte containing 0.05 M Ca(CH3COO)2 and 0.02 M (NH4)3PO4 was prepared, and plasma electrolytic oxidation was performed at 250 V for 3 minutes to obtain a porous TiO2 substrate with a thickness of 5 μm and a pore size of 1 μm. β-tricalcium phosphate powder (particle size 30 μm) and silver nanoparticles (particle size 20 nm) were mixed at a mass ratio of 97:3 and deposited using a plasma spraying process with a spraying power of 25 kW, a powder feed rate of 2 g / min, and a spraying distance of 100 mm to obtain a HA-Ag intermediate layer with a thickness of 20 μm. Using tetra(dimethylamino)titanium and N2 / H2 plasma as precursors, a dense TiN surface layer with a thickness of 60 nm was obtained by atomic layer deposition 300 cycles at 150 °C.
[0053] Step 3: Anneal at 350℃ in an inert atmosphere for 3 hours; load bioactive glass using the dip-coating method, with a suspension concentration of 0.2%, a dipping speed of 1 mm / s, and a dipping time of 90 seconds, repeating once.
[0054] Example 2 The 3D-printed Ti6Al4V porous implant for acetabular cups was used as the matrix, with a porosity of 70% and a pore size of 400μm.
[0055] A method for preparing a multifunctional gradient coating based on 3D printed implants includes the following steps: Step 1: Sandblasting is performed using white corundum particles (80μm in diameter) at a pressure of 0.3MPa to achieve a surface roughness Ra of 4μm; then, the surface is immersed in a mixed solution of HF / HNO3 (volume ratio 1:4) for acid etching for 3 minutes.
[0056] Step 2: Prepare the composite coating: An electrolyte containing 0.12 M Ca(H2PO4)2 and 0.06 M H3PO4 was prepared, and plasma electrolytic oxidation treatment was carried out at 320 V for 6 minutes to obtain a porous TiO2 substrate with a thickness of 7 μm and a pore size of 2 μm. Biphasic calcium phosphate powder (particle size 40 μm) and silver nanoparticles (particle size 25 nm) were mixed at a mass ratio of 94:6 and deposited using a plasma spraying process with a spraying power of 32 kW, a powder feed rate of 2 g / min, and a spraying distance of 130 mm to obtain a composite intermediate layer with a thickness of 25 μm. Using tetra(ethylmethylamino)titanium and N2 plasma as precursors, an atomic layer deposition cycle of 600 times was performed at 250 °C to obtain a TiN surface layer with a thickness of 120 nm.
[0057] Step 3: Anneal in a vacuum atmosphere at 400℃ for 2 hours; load bioactive glass using spin coating method, with a suspension mass concentration of 0.6%, spin coating at 1000 rpm for 60 seconds, and dry at 70℃ for 20 minutes.
[0058] Example 3 The 3D-printed Ti6Al4V porous implant for interbody fusion devices was used as the matrix, with a porosity of 80% and a pore size of 600μm.
[0059] A method for preparing a multifunctional gradient coating based on 3D printed implants includes the following steps: Step 1: Sandblasting is performed using alumina particles (100μm in diameter) at a pressure of 0.3MPa to achieve a surface roughness Ra of 5μm; then, the surface is immersed in a mixed solution of HF / HNO3 (volume ratio 1:5) for acid etching for 5 minutes.
[0060] Step 2: Prepare the composite coating: An electrolyte containing 0.2 M Ca3(PO4)2 and 0.1 M NaH2PO4 was prepared, and plasma electrolytic oxidation was performed at 400 V for 10 minutes to obtain a porous TiO2 substrate with a thickness of 10 μm and a pore size of 3 μm. Hydroxyapatite powder (50 μm particle size) and silver nanoparticles (30 nm particle size) were mixed at a mass ratio of 90:10 and deposited using a plasma spraying process with a spraying power of 40 kW, a powder feed rate of 2 g / min, and a spraying distance of 150 mm to obtain a composite intermediate layer with a thickness of 30 μm. Using TiCl4 and NH3 as precursors, an atomic layer deposition cycle of 800 times was performed at 350 °C to obtain a TiN surface layer with a thickness of 180 nm.
[0061] Step 3: Anneal at 450℃ in an inert atmosphere for 1 hour; load bioactive glass using spray deposition method, with a suspension mass concentration of 1.0%, a spraying distance of 15cm, a spraying time of 20 seconds, and allow to air dry.
[0062] Example 4 This embodiment provides a method for preparing a multifunctional gradient coating based on 3D-printed implants. A titanium alloy implant for chest wall repair is used as the substrate to prepare the multifunctional gradient coating. In this embodiment, a 3D-printed Ti6Al4V porous repair plate is selected as the substrate. The porosity of this repair plate is 60%, and the pore size is 300 μm.
[0063] Step 1: The surface of the repair plate is roughened by sandblasting with alumina particles with a diameter of 50 μm (pressure 0.3 MPa, Ra reaches 4 μm); then it is immersed in a 1:3 HF / HNO3 mixed solution for acid etching and activation for 2 minutes to expose the fresh titanium surface and construct nanoscale nucleation sites.
[0064] Step 2: Prepare a composite coating on the surface of the implant; In-situ generation of TiO2 substrate: An electrolyte containing 0.1 mol / L Ca(NO3)2 and 0.05 mol / L NaH2PO4 was prepared and discharged and oxidized at a processing voltage of 300V for 5 minutes to prepare a porous TiO2 substrate with a thickness of 8 μm, a porosity of 20%, and rich in calcium and phosphorus active ions in situ. Intermediate active antibacterial layer deposition: Hydroxyapatite powder (30 μm particle size) and silver nanoparticles (20 nm particle size) were mechanically mixed at a mass ratio of 95:5. The powder was co-deposited onto the surface of the bottom layer using a plasma spraying process (30 kW power, 2 g / min powder feed rate, 120 mm distance) to obtain a calcium phosphate ceramic-silver (HA-Ag) composite intermediate layer with a thickness of 25 μm. Surface TiN barrier layer deposition: The repair plate was placed in the ALD reaction chamber, and TiCl4 and NH3 were used as precursors for 500 cyclic deposition cycles at 200℃. Due to the superior conformal properties of atomic layer deposition, a dense, non-porous TiN surface film with a thickness of about 100 nm and grain size of less than 10 nm was uniformly coated on the microscopic surface and the porous interior of the shallow layer.
[0065] 3. Post-treatment and liquid-phase loading: First, the coated sample was placed in a muffle furnace and annealed at 400℃ under vacuum for 2 hours to eliminate residual interlayer stress. Subsequently, a suspension of micron-sized bioactive glass particles (particle size <1 μm) with a mass concentration of 0.5% was prepared. Using electrophoretic deposition (controlling the working voltage at 80V and the deposition time at 2 minutes), bioactive glass particles were loaded onto the TiN surface a second time, ultimately obtaining a personalized implant coating with multifunctional gradients.
[0066] The performance of the prepared coating samples was verified by performance testing.
[0067] Bond strength test: Tensile test was conducted according to ASTM F1044 standard. The bond strength between the gradient coating prepared in this embodiment and the substrate reached 22 MPa, which is significantly higher than the rigid requirement of ISO 13779-2 for surface coatings of bone implants to be greater than 15 MPa. This proves that the micro-mechanical interlocking effect provided by the PEO porous substrate is significant.
[0068] Biocompatibility and osseointegration evaluation: After 7 days of osteoblast (MG-63) culture, cell adhesion rate reached 88%, and alkaline phosphatase activity was significantly increased by 2.1 times compared to the uncoated pure titanium matrix. Twelve weeks after rabbit femoral condyle implantation, micro-CT and histological analysis showed a bone-implant contact ratio (BIC) of 65%, with no inflammatory response in the surrounding tissues, demonstrating excellent in vitro / in vivo osteogenic induction.
[0069] In vitro broad-spectrum antibacterial test: According to ISO 22196 standard, the coating showed an antibacterial rate of up to 99.2% against Staphylococcus aureus, confirming the release of Ag through the microchannels of the nano-TiN layer. + It exhibited strong contact toxicity and long-lasting antibacterial activity.
[0070] Potentiodynamic polarization and corrosion resistance test: Electrochemical test after immersion in simulated body fluid (SBF) for 14 days showed that the corrosion current density of the coating was only 0.8 μA / cm², which was 84% lower than that of pure titanium substrate (5 μA / cm²), fully demonstrating the excellent physical barrier function of nanoscale dense TiN surface film against body fluid erosion.
[0071] Example 5 A personalized biomedical implant includes a 3D-printed titanium alloy implant body and a multifunctional gradient coating attached to its surface. The multifunctional gradient coating comprises, from the inside out: 1. A porous TiO2 substrate with a thickness of 5-10 μm and a pore size of 1-3 μm, doped with calcium and phosphorus ions, generated in situ on the surface of the implant body by plasma electrolytic oxidation (PEO) process; 2. A calcium phosphate ceramic-silver composite intermediate layer with a thickness of 20-30 μm is deposited on the surface of the TiO2 substrate by plasma spraying (APS) process, wherein the mass percentage of silver nanoparticles is 3%-10%; 3. A dense TiN surface layer is completely covered and conformally encapsulated on the surface of the intermediate layer by atomic layer deposition (ALD) process, with an overall film thickness of 50-200 nm and an internal grain size of less than 10 nm; 4. The outermost surface of the TiN surface layer is further loaded with bioactive glass particles with a particle size of less than 1 μm through liquid phase deposition.
[0072] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.
Claims
1. A multifunctional gradient coating based on 3D printed implants, characterized in that, It includes a TiO2 bottom layer, a calcium phosphate ceramic-silver composite intermediate layer, and a TiN surface layer arranged sequentially from the inside out; The TiO2 bottom layer has a porous structure and is doped with calcium and phosphorus ions; The calcium phosphate ceramic-silver composite intermediate layer is composed of a calcium phosphate ceramic matrix and silver nanoparticles dispersed therein. The TiN surface layer is a dense, corrosion-resistant layer.
2. The multifunctional gradient coating based on 3D printed implants according to claim 1, characterized in that, The thickness of the calcium phosphate ceramic-silver interlayer is 20-30 μm, and the mass percentage of the silver nanoparticles is 3%-10%.
3. The multifunctional gradient coating based on 3D printed implants according to claim 1, characterized in that, The calcium phosphate ceramic matrix includes at least one of hydroxyapatite, β-tricalcium phosphate, or biphasic calcium phosphate.
4. The multifunctional gradient coating based on 3D printed implants according to claim 1, characterized in that, The TiN surface is also loaded with bioactive glass particles.
5. A method for preparing a multifunctional gradient coating based on a 3D-printed implant according to any one of claims 1-4, characterized in that, Includes the following steps: Step 1: Prepare a composite coating on the surface of the implant. The composite coating consists of a TiO2 bottom layer, a calcium phosphate ceramic-silver composite intermediate layer, and a TiN surface layer from the inside out. The implant is subjected to plasma electrolytic oxidation in an electrolyte containing calcium and phosphorus ions to generate a porous TiO2 bottom layer in situ on the implant surface, while calcium and phosphorus ions are incorporated into the TiO2 bottom layer. Calcium phosphorus ceramic powder is mixed with silver nanoparticles, and the mixed powder is deposited on the surface of the TiO2 bottom layer by plasma spraying process to form a phosphorus ceramic-silver composite intermediate layer. Atomic layer deposition was used to deposit a TiN surface layer on the surface of the phosphorus ceramic-silver composite intermediate layer using titanium and nitrogen precursors as raw materials. Step 2: Anneal the composite coating obtained in Step 1. After annealing, load bioactive glass particles onto the TiN surface using a liquid phase deposition process to obtain the multifunctional gradient coating.
6. The method for preparing a multifunctional gradient coating based on a 3D-printed implant according to claim 5, characterized in that, The procedure preceding step 1 includes a pretreatment step for the implant surface: The implant surface is sandblasted with sandblasting particles, and then the sandblasted implant is immersed in an acidic solution for acid etching for 1-5 minutes.
7. The method for preparing a multifunctional gradient coating based on a 3D-printed implant according to claim 5, characterized in that, The plasma electrolytic oxidation method is as follows: The implant is immersed in an electrolyte for plasma electrolytic oxidation at a voltage of 250-400V for 3-10 minutes. The concentration of calcium ions in the electrolyte is 0.05-0.2 mol / L, and the concentration of phosphorus ions is 0.02-0.1 mol / L.
8. The method for preparing a multifunctional gradient coating based on a 3D-printed implant according to claim 5, characterized in that, The atomic layer deposition method is as follows: The pulse time ratio of the titanium precursor to the nitrogen precursor is 1:(1-3), the deposition temperature is 150-350℃, and the number of cycles is 300-800.
9. The method for preparing a multifunctional gradient coating based on a 3D-printed implant according to claim 5, characterized in that, In step 2: the annealing temperature is 350-450℃, the time is 1-3 hours, and the annealing atmosphere is an inert gas atmosphere or a vacuum atmosphere.
10. The method for preparing a multifunctional gradient coating based on a 3D-printed implant according to claim 5, characterized in that, The wet deposition process is at least one of the following: dip-coating, spin-coating, or spray deposition.